2019 International Conference on Electromagnetics in Advanced Applications (ICEAA) 2019
DOI: 10.1109/iceaa.2019.8879106
|View full text |Cite
|
Sign up to set email alerts
|

Metamaterial Designs to Enhance Microwave Imaging Applications

Abstract: This paper presents an innovative metasurface design for emerging microwave brain imaging applications, such as stroke detection and monitoring. We have modelled different metamaterial designs in diverse setups, and have simulated their interactions with EM waves using CST Microwave Studio®. Our results have shown an enhancement of penetration for the transmitted signals when the metamaterial film is placed in contact with skin tissue. These results suggest that our design can be a significant hardware advance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…These two high dielectric substrates are bonded with with Rogers 3001 bonding film ( = 2.28, tan = 0.003). In previous work [ 18 , 34 ], we have performed several simulation studies to optimize this geometry for operating in contact with the human skin when immersed in our coupling medium.…”
Section: Materials and Methodsmentioning
confidence: 99%
“…These two high dielectric substrates are bonded with with Rogers 3001 bonding film ( = 2.28, tan = 0.003). In previous work [ 18 , 34 ], we have performed several simulation studies to optimize this geometry for operating in contact with the human skin when immersed in our coupling medium.…”
Section: Materials and Methodsmentioning
confidence: 99%
“…This dielectric medium is required for our system's antennas to operate efficiently in the desired frequency range [44]. One of our previous studies has already presented the MM unit cell design and the periodic structure based on this pattern [43], but we review and expand this methodology further.…”
Section: Methodsmentioning
confidence: 99%
“…To this end, this paper presents experiments with simplified planar phantoms and a cylindrical target mimicking bleeding in the brain as well as numerical simulations with a tomographic scanner and a brain model with a target. Our SRR-based MM film is first proposed as an antireflection coating able to improve impedance matching and, thus, to reduce reflection and to enhance transmission of microwave energy into a body region such as the head [43]. However, aware that a slight increase in overall transmission may not necessarily improve an MWI system's ability to detect bleeding in the brain, this paper focuses on examining whether the MM can enhance the "weak" signal scattered from a blood-like target, which is relevant to our application of interest.…”
Section: Introductionmentioning
confidence: 99%
“…The metallic pattern (thickness = 0.10 mm) is a variation of the Jerusalem Cross SRR. Our previous studies have already shown the MM unit cell design and the performance of MM layers based on this structure [13], [14].…”
Section: B Simulation Setupmentioning
confidence: 97%
“…In previous studies, we have examined various aspects of our work towards the design of a MWT scanner for brain imaging which incorporates a MM layer for signal enhancement and the DBIM-TwIST algorithm for recovering the unknown target of interest [13]- [15]. This paper examines in more details the potential of improving the quality of the reconstructed images for stroke detection and monitoring, by integrating MM technology in our MWT scanner.…”
Section: Introductionmentioning
confidence: 99%